2004
DOI: 10.1097/00124784-200405000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Local Health Department Partnerships With Faith-Based Organizations

Abstract: Collaboration between public health and faith communities is encouraged by national and state policies. The study in this article examined the prevalence, characteristics, and effectiveness of partnerships between faith-based organizations and local health departments in Wisconsin. Data were collected from local health departments using a 2-stage, cross-sectional survey. A subset analysis of partnerships that included faith-based organizations was conducted using descriptive, bivariate, and 2-level logit regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…Our research supports the assertions of others who have emphasized the potential value of LHD-FBO partnerships 47,48 and of local public health system partnerships, in general, to promote community health. 49 Using the program logic model as a strategic roadmap, and applying the portability materials to support operational execution, a robust potential would appear to exist for replication of the model elsewhere.…”
Section: Fostering Sustainability Impact and Scalability Of The Modelsupporting
confidence: 86%
“…Our research supports the assertions of others who have emphasized the potential value of LHD-FBO partnerships 47,48 and of local public health system partnerships, in general, to promote community health. 49 Using the program logic model as a strategic roadmap, and applying the portability materials to support operational execution, a robust potential would appear to exist for replication of the model elsewhere.…”
Section: Fostering Sustainability Impact and Scalability Of The Modelsupporting
confidence: 86%
“…It was apparent that congregants had previously had few opportunities to interact closely with health department personnel or other public health experts of whom to ask factual questions about HIV. This is consistent with prior research, which has found that most of the partnering organizations involved in congregational health activities are non-profit prevention and social service providers and not local health departments or other government public health agencies (Werber, Derose, DomĂ­nguez, & Mata, 2012; Zahner & Corrado, 2004). …”
Section: Lessons Learnedsupporting
confidence: 91%
“…Faith communities' health initiatives generally focus on general health maintenance, chronic disease prevention, and tobacco use prevention. [12][13][14][15][16][17] Some small-scale HIV prevention initiatives are described, [18][19][20] as are significant barriers to involvement in HIV prevention (eg, resource constraints, training needs, stigma). [20][21][22] The roles of values, religious doctrines, and beliefs explain the reluctance of many faith communities to become involved in HIV prevention.…”
mentioning
confidence: 99%